Description of Safety Riding Behavior and Knowledge in Adolescents in The South Tangerang Area - Ardimas Saputra; Alvian Ramadan; ABIZAR ALGIFARIH; Dewi Wulandari; Munaya Fauziah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Advances in science and technology make the growth rate of vehicles increasing and bring a positive impact on human welfare. The increasing use of vehicles also harms the highway, such as traffic density and vehicles have a very high level of accidents so that motor vehicles become one of the human killers through traffic accidents. Descriptive research method with qualitative approach with phenomenology method. Samples in this study as many as four (4) teenagers consisting of family and Relatives This study wants to explore the phenomenon experienced by teenagers in riding motorcycles. Factors that are the cause of traffic accidents are behavioral factors, knowledge factors, road factors (facilities and infrastructure), and weather factors, where human factors become the highest factors as the cause of traffic accidents. Driving a two-wheeled vehicle needs to be supported by good driving knowledge, gar traffic order can be carried out so that road safety can be realized, in addition to the enforcement of driving standards need to be considered such as the use of helmets and driving papers.